Understanding Concept of Virality in Social Media from Users’ Perspective - Atayeva, Nurana (2024)
The concept of virality is the subject that has been in the minds of many people for the past few years. In general terms, it is defined as a phenomenon where certain form of information spreads swiftly and widely across social networks. When applying this phenomenon to activities that are popular for ongoing generations, virality can mostly be observed in social media and content generated around it. Namely within past few years, short form videos have increasingly raised interest of public, and most of the content consumed nowadays in social media is through video formats. As a result, the interest in comprehending why certain type of content is preferred over another and becomes viral is continuously rising. Previously conducted research on a matter have identified that emotions, particularly positive ones, play as key drivers of virality, emphasizing the importance of content that elicits joy, excitement, or inspiration. However, much of this research has focused on quantitative analysis, leaving gaps in understanding from the users' perspective. Therefore, in order to complement existing knowledge, current study seeks to examine the concept of virality from users’ perspective as well as define whether viral content is regarded as the most engaging nowadays. Given objectives would consequently allow to identify drivers that cause virality of the content, which in turn would be able to assist organizations in optimization of their content creation strategies in social media. To conduct current research, qualitative research method with an exploratory purpose has been applied. Primary data was collected through semi-structured interviews with eleven participants involved from three different age groups. Collected data was analysed with the assistance of thematic analysis to identify recurring themes on a subject. However, as a complementary approach, descriptive comparative analysis was additionally adopted to provide straightforward results of the findings and allow readers to directly review responses of participants and clearly understand their perception on a subject. Results of the findings have revealed that users’ understanding of the concept directly matches academic definition of the phenomenon. Specifically, users define virality as a content, which is rapidly spreading across the platforms, reaching wide audiences, and becoming popular in an instant. In addition to the generalized definition of the term, users offer more insightful characteristics, explaining that viral content is described as visually appealing, short, authentic, emotionally impactful, and often humorous. Furthermore, current research offers additional findings into drivers that promote virality in social media as well as engagement attributes that influence interaction among the users. Lastly, results of current study offer managerial implications, suggesting brands to optimize con-tent creation strategies by considering the likability and shareability of content, focusing on engaging and shareable formats, and adapting viral content attributes to maintain relevance and relatability. On a conclusive note of the research, limitations and ethical considerations were examined as well as recommendations for future research shared.